HITLER AT HOME - Stratigakos, Despina (Yale University Press, 2015)
"At the height of the Third Reich, media outlets around the world showcased Hitler's homes to audiences eager for behind-the-scenes stories. After the war, fascination with Hitler's domestic life continued as soldiers and journalists searched his dwellings for insights into his psychology. The book's rich illustrations, many previously unpublished, offer readers a rare glimpse into the decisions involved in the making of Hitler's homes and into the sheer power of the propaganda that influenced how the world saw him."--Publisher's description